Atrial fibrillation and future risk of venous thromboembolism:the Tromsø study. (22nd November 2014) - Enga, K. F.; Rye‐Holmboe, I.; Hald, E. M.; Løchen, M.‐L.; Mathiesen, E. B.; Njølstad, I.; Wilsgaard, T.; Braekkan, S. K.; Hansen, J.‐B.
Summary Aims Whether atrial fibrillation is related to risk of venous thromboembolism (VTE) has not been extensively studied. Therefore, we investigated the association between atrial fibrillation and future risk of VTE in a population‐based cohort. Methods In total, 29 975 subjects were recruited from three surveys of the Tromsø study and followed from enrollment (1994–1995, 2001–2002 and 2007–2008) up to 2010. Incident events of atrial fibrillation and VTE during follow‐up were recorded. Information on potential confounders was obtained at baseline. Cox‐regression models with atrial fibrillation as time‐dependent variable were used to calculate hazard ratios (HRs) for VTE with 95% confidence intervals (CIs). Results During 16 years of median follow‐up, 1604 subjects were diagnosed with atrial fibrillation and 614 with incident VTE. The risk of VTE was substantially increased during the first 6 months after diagnosis of atrial fibrillation (HR, 8.44; 95% CI, 5.61–12.69), and remained increased throughout the study period (HR, 1.43; 95% CI, 1.43–1.99) compared with those without atrial fibrillation. Atrial fibrillation displayed higher risk estimates for pulmonary embolism (HR, 11.84; 95% CI, 6.80–20.63) than for deep vein thrombosis (HR, 6.20; 95% CI, 3.37–11.39) during the first 6 months, and was still associated with pulmonary embolism (HR, 1.96; 95% CI, 1.24–3.10) but not with deep vein thrombosis (HR, 1.08; 95% CI, 0.66–1.75) more than 6 months after diagnosis. Conclusion Atrial fibrillation was associated with increased risk of VTE, and pulmonary embolism in particular. Our findings support the concept that isolated pulmonary embolism may originate from right atrial thrombi due to atrial fibrillation.